A Local Health Situation Room for COVID-19: Recommendations for Decision-Making From a Higher Education Institution in Mexico - Ramos Herrera, Igor Martín; Romero Lozano, Diana Core; López Corona, Adolfo; Muñoz Valle, José Francisco; González Castañeda, Miguel Ernesto; Pérez Gómez, Héctor Raúl; Kasten Monges, Marina de Jesús; Ramos Solano, Moisés; Ruvalcaba Romero, Norma Alicia; Pérez Ávila, Fabian Alejandro; Yokogawa Teraoka, Patricia; Macedo Ojeda, Gabriela (Frontiers in Public Health, 2021)
Introduction: The Situation Room is a physical or virtual space where experts systematically analyze information to characterize a health situation, especially during emergencies. Decision-making processes are made towards solving the health needs, promoting collaboration among institutions and social sectors. This paper presents the context and circumstances that led the University of Guadalajara to install a local health situation room to address the COVID-19 pandemic at this institution based in the state of Jalisco, Mexico, a narrative is also made of its working processes as well as some of its results. Methods: The design of this situation room for COVID-19 was based on the methodology established by the Pan American Health Organization/World Health Organization. This local-type situation room was installed on February 12, 2020. The health problem was characterized, and strategic lines, objectives, and goals were established; the first analysis derived in an action plan deployed at the University of Guadalajara. The strategic lines were situational diagnosis, preventive actions, and containment strategies. Results: The situation room influenced the activities of the University of Guadalajara before the epidemic cases started in the state. One of the actions with the greatest impact was developing a mathematical model for predicting COVID-19 cases. Subsequently, new models have been developed according to the epidemiological evolution of the disease, helping manage the epidemic in the state. Another important result was the early closing of face-to-face university activities, reducing contagion risks and the mobility of more than 310 thousand students, faculty, and administrative personnel throughout Jalisco. Conclusions: A consequence of the closure was the confinement generated by the pandemic was the change to virtual meetings from April 2020 to date; but at the same time, this working format was a strength, since it influenced the decision of the university board to change all the academic activities to virtual format before other educational, economic and social activities in the state did. By April 2020, the situation room transcended its institutional boundaries, and was invited to participate at the Jalisco State's Health Committee. Its recommendations have helped maintain the state with one of Mexico's lowest COVID-19 incidence and mortality rates.